International activities of the Russian state in the field of social policy - Petrova D. D. (Law, Economics and Management, 2020)
the article provides a comprehensive analysis of the significance of international acts in the field of social insurance and social policy for the legal protection of the rights and freedoms of citizens of the Russian Federation.
Keywords: права и свободы человека; Организация объединённых наций; Экономический и социальный совет ООН; Всемирная организация здравоохранения (ВОЗ); human rights and freedoms; socio-economic rights and freedoms of man and citizen; United Nations; "international labour organization" (ILO); "international social security Association" (ISSA); UN Economic and social Council; world health organization (who); социально-экономические права и свободы человека и гражданина; Международная организация труда (МОТ); Международная ассоциация социального обеспечения (МАСО)